GOOD AND CORRECT USE OF INDONESIAN LANGUAGE IN CLASS MEDICAL RECORDS AND HEALTH INFORMATION 1B - Ertinawati, Yuni; Sugih, Erfa Purnama; Aprillanita, Nabela; Nursyifa, Tiara (Media Inovasi Pendidikan dan Publikasi, 2024)
Good and correct use of Indonesian in medical record and health information class 1B The research results show that there are several obstacles to the good and correct use of Indonesian in medical record and health information class 1B,, including slang, regional languages ​​and habits. The conclusion is that language is very important for everyone, especially for us as students. The research results show that language use in the campus environment largely depends on the situation and conditions. If we are in a formal environment, we will speak directly, politely, politely, and effectively and efficiently to maintain Indonesian. However, it is different when we are in an informal environment, such as hanging out with classmates using language that is easy to understand.